Spiritual intelligence on health behaviours among Malaysian university students in a Malaysian public university: the mediating role of self efficacy - Omar Dev, Roxana Dev; Tengku Kamalden, Tengku Fadilah; Soh, Kim Geok; Mohd Ayub, Ahmad Fauzi; Ismail, Ismi Arif (Universiti Malaysia Pahang, 2018)
University students experience a substantial amount of change where they progress from the highly controlled setting of school to the self-motivated environment of the university. Many changes which involve social, financial, and environment elements, can be a burden to the students putting them at risk in negative health behaviours. Negative health behaviours among university students are a course of concern since they have a tendency to be carried into adulthood which can possibly cause the emergence of chronic disease at a younger age. Spiritual intelligence together with self-efficacy is seen to promote better health behaviour. Therefore, the purpose of the study was to investigate the relationship between spiritual intelligence and self-efficacy on health behaviours among university students in Universiti Putra Malaysia, Malaysia. A correlational study was conducted on 400 undergraduate university students who lived on campus and were chosen through stratified random sampling technique using closed ended questionnnaires (The Spiritual Self-Report Inventory, General Self Efficacy Scale and a modified version of Health Style Questionnaire). Pearson correlation and structural equation modelling were used to explore association between these aspects. Spiritual intelligence, self-efficacy and health behaviour were significantly correlated. Self-efficacy showed a partial mediation effect towards the relationship between spiritual intelligence and promoting health behaviour (p=0.0001). Thus, there was an association between spiritual intelligence with health behaviour, and self-efficacy with health behaviour. It is interpreted that spiritual intelligence can boost positive health behaviour and it is associated with self-efficacy relevantly gives benefit to health behaviour. Such data have important implications for both health practice and policy especially for higher education institutions.